Transplanting allo‐islets without immunosuppression. (March 2014) - Ludwig, Barbara; Reichel, Andreas; Steffen, Anja; Zimmermann, Baruch; Colton, Clark K.; Ludwig, Stefan; Kersting, Stephan; Bonifacio, Ezio; Solimena, Michele; Gendler, Zohar; Rotem, Avi; Barkai, Uriel; et al.
<x xml:space="preserve">Abstract</x> Introduction Pancreatic islet transplantation is currently restricted to patients with critical metabolic lability due to long‐term need for immunosuppression and a persistent shortage of donor organs [1–3]. To overcome these obstacles we have developed a strategy for islet macroencapsulation that provides sufficient immune‐isolation whereas regulated islet graft function is maintained [4–8]. Case Report and Methods A 63 year old patient with type 1 diabetes and severe metabolic lability was transplanted with isolated islets (2, 000 islets/kgBW) encapsulated in an oxygenated chamber system composed of immune‐isolating alginate and polymembrane covers. Via a small abdominal incision, a pre‐peritoneal pocket for the chamber was dissected, connected oxygen ports were implanted subcutaneously. No immunosuppressive therapy was applied. Results The procedure was surgically straightforward and without complications. We could demonstrate persistent graft function by detection of endogenous insulin and c‐peptide secretion proving islet viability and function. This observation was accompanied by persistent lowering in HbA1c despite reduction in insulin requirement. For oxygenation of the non‐vascularized and therefore immune‐shielded islet graft, the chamber‐integrated gas reservoir was replenished daily via the implanted ports without complications. Conclusion This encapsulation strategy was for the first time applied to allogeneic human islet transplantation in man. We demonstrated a persistent graft function with regulated insulin secretion without any immunosuppressive therapy. This novel concept may allow for future widespread application for cell‐based therapies. References [1] 2007 update on allogeneic islet transplantation from the Collaborative Islet Transplant Registry (CITR). Cell Transplant 2009; 18: 753–767. [2] Ludwig, B., Ludwig, S., Steffen, A., Saeger, H.D., Bornstein, S.R. Islet versus pancreas transplantation in type 1 diabetes: competitive or complementary? Curr Diab Rep 2010; 10: 506–511. [3] Mccall, M., James Shapiro, A.M. Update on islet transplantation. Cold Spring Harb Perspect Med 2012; 2: a007823. [4] Barkai, U., Weir G.C., Colton C.K. et al. Enhanced Oxygen Supply Improves Islet Viability in a New Bioartificial Pancreas. Cell Transplant 2013; 22(8): 1463–1476 [5] Ludwig, B., Rotem A., Schmid J. et al. Improvement of islet function in a bioartificial pancreas by enhanced oxygen supply and growth hormone releasing hormone agonist. Proc Natl Acad Sci U S A 2012; 109: 5022–5027. [6] Ludwig, B., Zimmermann B., Steffen A. et al. A novel device for islet transplantation providing immune protection and oxygen supply. Horm Metab Res 2010; 42: 918–922. [7] Neufeld, T., Ludwig B., Barkai U. et al. The efficacy of an immunoisolating membrane system for islet xenotransplantation in minipigs. PLoS One 2013; 8: e70150. [8] Ludwig, B., Reichel A, Steffen A et al. Transplantation of human islets without immunosuppression. PNAS 2013; 110: 19054–19058.